Novel bio-hybrid drag induced wind turbine - Sanderasagran, Ashwindran Naidu; Azizuddin, Abd Aziz; Oumer, Ahmed Nurye (2021)
In the world of rapid growing economy, energy consumption by power industry and human are drastically rising which is leading to an energy crisis situation. Today several countries are investing their resources on the development of renewable energy; wind power generation. 1. Pollution Increasing carbon emission by industry and humans activities had impacted global climate which lead to increasing greenhouse gases at the atmosphere year by year regardless the campaign and regulations initiated by the government and NGO. 2. Wind turbine's design for low-wind speed Design modification were done on wind turbine by engineers in order to adapt the wind speed of the desired geographical area. Researches indicates that, drag driven wind turbines such as Savonius and Darrieus VAWTs are suitable in harvesting wind energy in low wind speed potential.